ANALISIS TENTANG FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA BATURIJAL HULU KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Yunita, Iis; Eddison, Ahmad; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is based on the factors that cause children to drop out of school. In the role of the sub-district to be precise in the village of Baturijal Hulu, there are children who quit school or drop out of school. This can see the phenomenon and make observations and conduct interviews with one of the parents of children who have dropped out of school there, namely Mrs. Mita. According to Mrs. Mita, I quit second grade high school because of the influence of the social environment. He went out to play with his friends almost every night out, as parents often forbade him to go out too often and told him to study. to the extent that almost every day the mother gets angry telling her to go to school. Based on the formulation of the problem in this study, what are the factors that cause children to drop out of school. While the aim of the researcher is to determine the factors that cause children to drop out of school and the benefits of this study to increase knowledge that education is very important in life. Because education is very important in achieving dreams, dreams and the future. This research method is qualitative, the informants in this study amounted to 15 children who met the criteria as informants using purposive sampling technique. Data collection techniques used in this study were observation, interview and documentation. For data analysis techniques in this study are data reduetition (data reduction), data display (data presentation), and verification (drawing conclusions). The causes of children dropping out of school are caused by the weak family economy, less attention from parents about the importance of children's education. , lack of ability, lack of interest in learning, the influence of the living environment, and not graduating or embarrassed.Key Words: Factors, School Dropout Children